Upper semicontinuity of global attractors for quasilinear parabolic equations on unbounded thin domains - Silva, Ricardo P. [UNESP] (Springer, 2015)
We consider the asymptotic behavior of quasilinear parabolic equations posed in a family of unbounded domains that degenerates onto a lower dimensional set. Considering an auxiliary family of weighted Sobolev spaces we show the existence of global attractors and we analyze convergence properties of the solutions as well of the attractors.
Keywords: Thin domains; p-Laplacian; Global attractors